Recombinant Mycobacterium bovis BCG-Based HIV Vaccine: Failures and Promising Approaches for a Successful Vaccine Strategy - Joan Joseph-Munné; Milena Maya-Hoyos; Narcís Saubi; Santiago Perez; Miguel Angel Martinez Lopez; Eder Baron; Carlos Yesid Soto (Vaccines)
During 2022, AIDS claimed a life every minute and about 9.2 million HIV-infected people were not on treatment. In addition, a person living with HIV is estimated to be 20–30 times more susceptible to developing active tuberculosis. Every year, 130,000 infants are newly infected, with vertical transmission being the main cause of pediatric HIV infection. Thus, the development of an effective, safe, and accessible vaccine for neonates and/or adults is an urgent need to prevent or control HIV infection or progression to AIDS. An effective HIV vaccine should induce long-lasting mucosal immunity, broadly neutralizing antibodies, innate immunity, and robust stimulation of CD4+ and CD8+ T-cell responses. Recombinant BCG is a promising live-attenuated bacterial vaccine vector because of its capacity to stimulate T-cell immunity. As a slow-growing microorganism, it provides prolonged low-level antigenic exposure upon infecting macrophages and APCs, potentially stimulating both effector and memory T-cell responses. BCG is considered safe and is currently administered to 80% of infants in countries where it is part of the national immunization program. Additionally, BCG offers several benefits as a live vaccine vehicle since it is cost-effective, easy to mass-produce, and heat stable. It is also well-suited for newborns, as maternal antibodies do not interfere with its efficacy. Furthermore, BCG has a strong safety profile, having been administered to over three billion people as a TB vaccine. In this review, we provide an extensive summary of the literature relating to immunogenicity studies in animal models performed since 2011. Moreover, we provide a comprehensive analysis of the key factors influencing the design of recombinant BCG as a live vaccine vehicle: (i) expression vectors; (ii) selection of HIV immunogen; (iii) promoters to regulate gene expression; (iv) BCG strain and BCG codon optimization; (v) genetic plasmid stability; (vi) influence of preexisting immunity, route, and dose immunization; and (vii) safety profile.